ESR Essentials: radiomics—practice recommendations by the European Society of Medical Imaging Informatics - Santinha, João; Pinto dos Santos, Daniel; Laqua, Fabian; Visser, Jacob J.; Groot Lipman, Kevin B.W.; Dietzel, Matthias; Klontzas, Michail E.; Cuocolo, Renato; Gitto, Salvatore; Akinci D’Antonoli, Tugba (European Radiology, 2024)
Abstract: Radiomics is a method to extract detailed information from diagnostic images that cannot be perceived by the naked eye. Although radiomics research carries great potential to improve clinical decision-making, its inherent methodological complexities make it difficult to comprehend every step of the analysis, often causing reproducibility and generalizability issues that hinder clinical adoption. Critical steps in the radiomics analysis and model development pipeline—such as image, application of image filters, and selection of feature extraction parameters—can greatly affect the values of radiomic features. Moreover, common errors in data partitioning, model comparison, fine-tuning, assessment, and calibration can reduce reproducibility and impede clinical translation. Clinical adoption of radiomics also requires a deep understanding of model explainability and the development of intuitive interpretations of radiomic features. To address these challenges, it is essential for radiomics model developers and clinicians to be well-versed in current best practices. Proper knowledge and application of these practices is crucial for accurate radiomics feature extraction, robust model development, and thorough assessment, ultimately increasing reproducibility, generalizability, and the likelihood of successful clinical translation. In this article, we have provided researchers with our recommendations along with practical examples to facilitate good research practices in radiomics. Key Points: Radiomics’ inherent methodological complexity should be understood to ensure rigorous radiomic model development to improve clinical decision-making. Adherence to radiomics-specific checklists and quality assessment tools ensures methodological rigor. Use of standardized radiomics tools and best practices enhances clinical translation of radiomics models.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Feature extraction; Image pre-processing; Radiomics; Radiomics model training and assessment; Reproducibility